The Concept of Digital Twin and Digital Shadow in Manufacturing - Bergs, Thomas; Gierlings, Sascha; Auerbach, Thomas; Klink, Andreas; Schraknepper, Daniel; Augspurger, Thorsten (Procedia CIRP, 2021)
There still is a lacking comprehensive understanding of the relevant terms Digital Twin (DT) and Digital Shadow (DS) in particular within the application on the field of manufacturing technology. However, a common, transparent understanding of the concept and its requirements interferes with the implementation and application of these powerful tools. In this sense, the following publication gives a new definition of the concept within the field of manufacturing technology and shows specific applications.